2015
DOI: 10.1159/000437431
|View full text |Cite
|
Sign up to set email alerts
|

Social Function and Frontopolar Activation during a Cognitive Task in Patients with Bipolar Disorder

Abstract: Background: It is important to understand the neural basis of functional impairments in patients with bipolar disorder (BD) in order to be able to address the recovery. Recently, neurocognitive impairment emerged as a predictor of psychosocial function. A number of functional brain imaging studies have shown that social function is associated with activation of the prefrontal cortex during a cognitive task in healthy adults, and in patients with major depressive disorder and schizophrenia. However, few studies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(7 citation statements)
references
References 58 publications
1
6
0
Order By: Relevance
“…There is less extensive literature on using WM tasks with fNIRS, but, again, bilateral activation has been found. 92,113 Consistent with extensive literature, [94][95][96][97][98][99][100][101][102][103][104][105][106][107][108][109][112][113][114] we found significantly decreased, and possibly delayed, prefrontal haemodynamic responses in depressed patients in the VF task and, less certainly, in the n-back task. For the VF task we found a significant negative correlation between MADRS score and the haemodynamic response in the LVF cortex in patients.…”
Section: Near-infrared Spectroscopy Studysupporting
confidence: 91%
See 1 more Smart Citation
“…There is less extensive literature on using WM tasks with fNIRS, but, again, bilateral activation has been found. 92,113 Consistent with extensive literature, [94][95][96][97][98][99][100][101][102][103][104][105][106][107][108][109][112][113][114] we found significantly decreased, and possibly delayed, prefrontal haemodynamic responses in depressed patients in the VF task and, less certainly, in the n-back task. For the VF task we found a significant negative correlation between MADRS score and the haemodynamic response in the LVF cortex in patients.…”
Section: Near-infrared Spectroscopy Studysupporting
confidence: 91%
“…[107][108][109] There is some uncertainty over whether this is a state or trait abnormality, as some studies have found restored activation to a VF task following treatment 110 and increased activation has been seen in hypomanic patients, 108 whereas blunted responses have been found in remitted depressed patients 111 and euthymic bipolar patients 109 or failure to normalise after antidepressant treatment in depressed patients. 99 WM has been less investigated using fNIRS, but studies have also shown a decrease in lateral frontal haemodynamic responses in depression, [112][113][114] which were associated with decreased performance in one study.…”
Section: Background and Objectivesmentioning
confidence: 99%
“…Such research does not, however, improve clinicians’ abilities to diagnose a mood disorder. Brain activity observed during a verbal fluency task may be an objective marker that can differentiate between MDD and BD with depression (Benedetti and Bollettini, 2014; Kinoshita et al, 2016), but consistent results have not been obtained (Nishimura et al, 2015). Thus, although many possible biomarkers have been proposed to differentiate a number of psychiatric disorders, there is still considerable research needed to establish cost-effective and clinically useful indicators that can be used to aid in accurate diagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…122 A cognitive analysis of BD patients revealed that better social performance was linked with higher activation in the right PFC. 123 The HbO variations of hypomanic BD patients were signi¯cantly higher than those of depressed BD patients in the left dorsolateral PFC. 124 The depressive and euthymic states in BD patients were di®erentiated based on HbO levels in the left temporal region, whereas the intensity of the HbO change revealed the severity of the symptoms.…”
Section: Verbal°uency Taskmentioning
confidence: 93%